Understanding mathematical concepts of comparison materials based on webquiz - Febrilia, Yeyen; Adi, Banu Setyo; Amelia, Maria Agustina; Aminah, Siti; Saputra, Julianto (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Comparison is a complex mathematical concept that often leads to misconceptions among students. This study is focused on evaluating the understanding of comparative material among PGSD students at Sanata Dharma University, Yogyakarta.Aim: The main objective of this study is to assess the level of understanding of comparative material concepts, including mathematical comparison, comparative mathematical understanding, the ratio of turning around, and mathematical understanding of scale, among the students.Method: A survey method was employed for this research. The study involved 46 PGSD students at Sanata Dharma University who participated through Quizizz and Google Drive. The instrument consisted of 10 conceptual questions and 5 discussion questions, followed by reinforcement material to enhance understanding. Participants were instructed to complete questions via https://join.quizizz.com, and the completed steps were submitted through Google Drive.Result: The analysis revealed that 1) the mathematical understanding of the concept of comparison was at 83%; 2) comparative mathematical understanding stood at 68.67%; 3) the mathematical understanding of the ratio of turning around was 73.2%; and 4) the mathematical understanding of scale was at 83%.Conclusion: The study indicates that the understanding of mathematical concepts related to comparative material among PGSD students at Sanata Dharma University is in the high category. These findings could serve as a foundation for further instructional design aimed at bolstering comparative concept understanding.